Fiscal Policy in Maritime Economics: Implications for Growth and Sustainability - Mudakir Mudakir; Muhammad Zilal Hamzah; Eleonora Sofilda (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research explores the impact of fiscal policies on maritime economics, focusing on macroeconomic stability, sector-specific resilience, and sustainability initiatives within maritime industries. Through qualitative analysis and expert perspectives, the study examines how fiscal interventions influence economic growth, address regional disparities, and promote environmental stewardship in maritime sectors. Key findings highlight the effectiveness of fiscal tools in stabilizing economic fluctuations, fostering innovation, and enhancing industry competitiveness. Challenges such as regulatory complexities, uneven distribution of fiscal benefits, and the need for enhanced fiscal transparency are also discussed. The research underscores the importance of tailored fiscal strategies that support inclusive growth, sustainable development, and global competitiveness in maritime economies.